EDUKASI KESIAPSIAGAAN BENCANA BAGI SISWA SEKOLAH DASAR MELALUI PENDEKATAN SEKOLAH AMAN BENCANA (SAB) DI SD NEGERI LAWE TUA KABUPATEN ACEH TENGGARA - Risnawati, Ira; Siddiq, Muhraza; Siregar, Ripai; Prima, Armanda (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Indonesia is a disaster-prone country due to its location on the Pacific Ring of Fire and the intersection of major tectonic plates, making disaster preparedness an urgent need, especially for elementary school students who are considered a vulnerable group. SD Negeri Lawe Tua in Aceh Tenggara District is located in an area highly prone to flash floods and landslides and has not yet implemented a structured disaster mitigation program. This community service program aims to improve student preparedness and strengthen school capacity through the Safe School Program (Sekolah Aman Bencana/SAB). The activities included disaster education, evacuation route training, establishment of a School Disaster Preparedness Team (SDPT), installation of evacuation signs and SOPs, and a full-scale evacuation drill. Evaluation was conducted using pre-tests and post-tests, evacuation time measurements, and observation of student behavior and teacher involvement. The results showed a significant increase in students’ knowledge, with average scores rising from 36% (pre-test) to 86% (post-test), reflecting a 50% improvement. Understanding of evacuation routes increased the most, reaching 65%. Teachers also demonstrated better readiness as facilitators, and the school gained more complete disaster mitigation facilities. In conclusion, SAB-based preparedness education is proven effective in enhancing students’ ability to respond to emergencies and strengthening school disaster management. The program is recommended for sustainable implementation and replication in other disaster-prone schools.